IL-17A secreted from lymphatic endothelial cells promotes tumorigenesis by upregulation of PD-L1 in hepatoma stem cells - Wei, Yuanyan; Shi, Danfang; Liang, Ziwei; Liu, Yuming; Li, Yinan; Xing, Yang; Liu, Weitao; Ai, Zhilong; Zhuang, Jianhui; Chen, Xiaoning; Gao, Qiang; Jiang, Jianhai (Journal of hepatology, 2019)
[Display omitted] •Hepatoma stem cells preferentially interact with lymphatic endothelial cells.•Interaction of hepatoma stem cells with lymphatic endothelial cells upregulates IL-17A.•IL-17A promotes hepatoma stem cell self-renewal and immune escape.•IL-17A is highly expressed in hepatoma. The microenvironment regulates hepatoma stem cell behavior. However, the contributions of lymphatic endothelial cells to the hepatoma stem cell niche remain largely unknown; we aimed to analyze this contribution and elucidate the mechanisms behind it. Associations between lymphatic endothelial cells and CD133+ hepatoma stem cells were analyzed by immunofluorescence and adhesion assays; with the effects of their association on IL-17A expression examined using western blot, quantitative reverse transcription PCR and luciferase reporter assay. The effects of IL-17A on the self-renewal and tumorigenesis of hepatoma stem cells were examined using sphere and tumor formation assays. The role of IL-17A in immune escape by hepatoma stem cells was examined using flow cytometry. The expression of IL-17A in hepatoma tissues was examined using immunohistochemistry. CD133+ hepatoma stem cells preferentially interact with lymphatic endothelial cells. The interaction between the mannose receptor and high-mannose type N-glycans mediates the interaction between CD133+ hepatoma stem cells and lymphatic endothelial cells. This interaction activates cytokine IL-17A expression in lymphatic endothelial cells. IL-17A promotes the self-renewal of hepatoma stem cells. It also promotes their immune escape, partly through upregulation of PD-L1. Interactions between lymphatic endothelial cells and hepatoma stem cells promote the self-renewal and immune escape of hepatoma stem cells, by activating IL-17A signaling. Thus, inhibiting IL-17A signaling may be a promising approach for hepatoma treatment. The microenvironment is crucial for the self-renewal and development of hepatoma stem cells, which lead to the development of liver cancer. Lymphatic endothelial cells are an important component of this niche microenvironment, helping hepatoma stem cells to self-renew and escape immune attack, by upregulating IL-17A signaling. Thus, targeting IL-17A signaling is a potential strategy for the treatment of hepatoma.